The simulation research of ionospheric side-scatter ionogram - Na Wei (2012 10th International Symposium on Antennas, Propagation and EM Theory, 2012)
Studies on ionospheric side-scatter are of great significance to MIMO OTHR. The side-scatter ionogram includes most information of side-scatter channel characteristics. Thus, the simulations of ionospheric side-scatter ionogram are developed in order to give a preliminary understanding of the side-scatter propagation, then the preliminary results are given.